The Social Startup Toolkit - Ely, Philip (UnLtd - Foundation for Social Entrepreneurs, 2018)
We've designed this toolkit for anyone with an ambition to do a social good, through the creation of projects or ventures that (ultimately) will become financially sustainable. The toolkit contains essential and practical tools - including the Social Enterprise Blueprint - to help you model your business in development.